Impact of the COVID Pandemic on Prostate Cancer Diagnosis and Treatment: Results from a Croatian Tertiary Referral Center - Iva Bukša; Klara Smolić; Antonija Srok; Josip Španjol; Kristian Krpina (Acta Clinica Croatica)
The COVID-19 pandemic had a negative impact on the treatment of diseases other than COVID. The aim of our study was to demonstrate the impact it had on the diagnosis and treatment of patients with prostate cancer. By reviewing the work performed at the Clinic of Urology of the Clinical Hospital Centre Rijeka, we compared the following data for the period before the pandemic (2018) and the period during the pandemic (2021): number of prostate biopsies performed, number of newly-diagnosed cancers, PSA levels at biopsy, waiting time from the diagnosis to start of the treatment, stage of disease at biopsy and stage after prostatectomy, and finally the treatment options used. The results confirm the hypothesis that the pandemic had a negative impact on both diagnosis and treatment. The number of newly-diagnosed patients decreased by 37.24%, which correlates with a lower number of all prostate biopsies. We also noted a longer time to the start of the treatment for patients and an increase in poorer pathohistological outcomes after radical prostatectomy. Due to the higher disease stages, radiotherapy and chemotherapy were used more frequently.